Impurity Tracking Enables Enhanced Control and Reproducibility of Hybrid Perovskite Vapor Deposition. - Borchert, Juliane; Levchuk, Ievgen; Snoek, Lavina C.; Rothmann, Mathias Uller; Haver, Renee; Snaith, Henry J.; Brabec, Christoph; Herz, Laura M.; Johnston, Michael B. (ACS Applied Materials and Interfaces, 2019)
Metal halide perovskite semiconductors have the potential to enable low-cost, flexible, and efficient solar cells for a wide range of applications. Physical vapor deposition by co-evaporation of precursors is a method that results in very smooth and pinhole-free perovskite thin films and allows excellent control over film thickness and composition. However, for a deposition method to become industrially scalable, reproducible process control and high device yields are essential. Unfortunately, to date, the control and reproducibility of evaporating organic precursors such as methylammonium iodide (MAI) have proved extremely challenging. We show that the established method of controlling the evaporation rate of MAI with quartz microbalances (QMBs) is critically sensitive to the concentration of the impurities MAH2PO3 and MAH2PO2 that are usually present in MAI after synthesis. Therefore, controlling the deposition rate of MAI with QMBs is unreliable since the concentration of such impurities typically varies from one batch of MAI to another and even during the course of a deposition. However once reliable control of MAI deposition is achieved, we find that the presence of precursor impurities during perovskite deposition does not degrade the solar cell performance. Our results indicate that as long as precursor deposition rates are well controlled, physical vapor deposition will allow high solar cell device yields even if the purity of precursors changes from one run to another.
Keywords: solar cells; perovskites; hybrid metal-halide perovskites; co-evaporation; impurities; thermal evaporation; methylammonium iodide; residual gas analysis